Secoisolariciresinol Diglucoside Improves Ovarian Reserve in Aging Mouse by Inhibiting Oxidative Stress - He, XueLai; Wang, Yong; Wu, MeiQi; Wei, JiangChun; Sun, XianDuo; Wang, AnHua; Hu, GaoSheng; Jia, JingMing (Frontiers in Molecular Biosciences, 2022)
Ovarian reserve is a key factor in the reproductive function of the ovaries. Ovarian aging is characterized by a gradual decline in the quantity and quality of follicles. The underlying mechanism of ovarian aging is complex and age-related oxidative stress is considered one of the most likely factors. Secoisolariciresinol diglucoside (SDG) has been shown to have good scavenging ability against reactive oxygen species (ROS) which slowly accumulates in ovarian tissues. However, it is unknown whether SDG had beneficial effects on aging ovaries. In this study, we used 37-week-old female C57BL/6J mouse as a natural reproductive aging model to evaluate the role of SDG in ovarian aging. SDG (7 and 70 mg/kg) intragastric administration was performed in the mice daily. After 8 weeks, the effects of SDG on aging ovaries were evaluated by counting the number of follicles and the expression of follicle-stimulating hormone receptors (FSHR) in the ovary. The mechanism of SDG on the aging ovaries was further explored through ovarian metabolomics. It was found that SDG can effectively increase the number of growing follicles and increase the expression of the FSHR protein. The metabolomics results showed that the ovaries in the SDG intervention group achieved better uptake and transport of nutrients, including amino acids and glucose that are necessary for the development of oocytes. At the same time, the ovaries of the SDG intervention group showed that the drug reduced ROS generation. Additionally, we found that ovarian telomere length and ovarian mitochondrial DNA copy number that are highly susceptible to ROS damage and are also related to aging. The results showed that SDG can significantly increase mitochondrial DNA copy number and slow down the process of telomere shortening. These data indicate that SDG improves ovarian reserve by inhibiting oxidative stress.